Propuesta para el diseño de facilidades turísticas en la Represa Río Grande en Chone, Manabí - Zambrano Alcívar, José Luis (2023)
The purpose of this work was to design tourist facilities at the Rio Grande Dam in the Chone canton. For this purpose, the research was structured in three stages. The first stage consisted of a diagnosis of the territory; the second stage consisted of a market study; and the third stage consisted of designing tourism facilities for the dam. The characterization of the territory allowed identifying the existence of elements such as the scenic beauty present in the dam as a determining factor in the involvement of the area towards tourism, in the same sense, there was a great interest on the part of the receiving community, local government, academia and NGOs, in working together. Once the availability to collaborate was known, 195 potential visitors to the dam were surveyed with the objective of finding out, according to their criteria, which activities and/or facilities would motivate their visit, determining that typical food, viewpoints, trails, and boat and/or kayak rides were the most highly valued. These constructions are expected to have the participation of 80% of INBAR and 20% of the GAD Chone and the community, in a collaborative work. The technical standards and criteria that must be met for the construction of the tourist facilities are also specified.